Kinetics and thermodynamics of dissolved petroleum hydrocarbons in sediment under sophorolipid application and their effects on oil behaviour end-results in marine environment. Issue 72 (26th September 2017) - Li, Haoshuai; Zhuang, Xiaohong; Bao, Mutai
Abstract : The behaviour end-result of dissolved petroleum hydrocarbons (DPHs) is known to interact with sediments in marine environments. Abstract : The behaviour end-result of dissolved petroleum hydrocarbons (DPHs) is known to interact with sediments in marine environments. The simulated experiments presented here investigated the progress of behaviour end-results, including the adsorption isotherm, adsorption kinetics, and thermodynamics parameters, and focuses specifically on the effects of factors in the presence of sophorolipids. The results show that there is good agreement between the experimental data and the Lagergren pseudo-second-order model ( R 2 = 0.968). A Freundlich isotherm model ( R 2 = 0.924) was derived to describe the adsorption process, where Δ H θ and Δ S θ were 39.1 kJ mol −1 and 104.0 J (K mol) −1, respectively. Such calculations indicated that this process is part of a complex physical and chemical reaction and is an endothermic reaction. It is worth noting that randomness at the solid-solution interface increased during the adsorption process. The adsorption sites met the need of petroleum hydrocarbon molecules when the sediment concentration reached 3 g L −1 . The dominant sediment grain size fractions were <150 μm, and the total adsorption quantity of the fraction accounted for 0.27. The DPHs adsorbed hydrocarbons more easily when a chemical dispersant, GM-2, was applied, but at the same depth, the hydrocarbon content adsorbed by the sediment under biosurfactant application was relatively low. It is significant that sediment samples had a lower adsorption capacity when using a sophorolipid as a biosurfactant, rather than a rhamnolipid. Understanding the adsorption of DPHs onto sediment under sophorolipid application will broaden the understanding of heavy oil transport mechanisms and will provide a theoretical basis for remediation of areas with serious oil pollution.